Evaluation of the Effect of Chatbot in Improving Customer Interaction and Satisfaction in Online Marketing in Indonesia - Gatot Wijayanto; Yutiandry Rivai; Agnes Alvionita; Sri Wahyuni Wildah; Jushermi Jushermi (West Science Business and Management, 2023)
The present study explores the revolutionary effects of chatbots on consumer interaction and satisfaction in the rapidly developing field of online marketing in Indonesia. Using a mixed-methods research design that includes both qualitative and quantitative interviewing, this study investigates the various ways in which chatbots impact both consumers and companies. The quantitative data shows a substantial correlation between the use of chatbots and higher levels of customer satisfaction, with a sizable percentage of respondents preferring the speed and convenience of chatbot interactions. Qualitative insights shed light on the reasons behind companies' adoption of chatbots as well as the difficulties encountered in their deployment. Overall, this study highlights how important chatbots are to creating satisfying consumer experiences in Indonesia's online marketing industry and provides insightful information for companies looking to maximize their customer engagement tactics.